Screening of Asymptomatic COVID-19 Cases from the Aspect of Virus Spread - Mesut Ortatatli; Zahir Kilic; Ahu Pakdemirli; Levent Kenar (Acta Clinica Croatica)
The COVID-19 pandemic has hit the entire world. While symptomatic patients can be taken out of the infection chain, asymptomatic cases are very important for the spread of SARS-CoV-2. We investigated the relationship between isolating asymptomatic COVID-19 cases with close contacts by identifying and breaking the infection chain. This study included 3 asymptomatic COVID-19 cases identified during screening and 25 close contacts as a result of filiation. Twenty-five people with close contact were classified into groups A (n=8), B (n=6) and C (n=11). On SARS-CoV-2 PCR tests performed in close contacts, all of them were negative on day 0, whereas two group C subjects were positive on day 7. On antibody test applied on day 28, six subjects were positive in group A, two subjects were positive in group B, and one subject was positive in group C. A statistically significant decrease was observed in the number of infected people in the group where asymptomatic cases were identified and removed (p=0.04). It was determined that asymptomatic COVID-19 cases who were not isolated from the community had a 5-fold increased risk of infection. Screening and identification of asymptomatic cases is also essential to augment the effectiveness of quarantine and isolation measures.